Variants in the mitochondrial genome sequence of Oryctes rhinoceros (Coleoptera: Scarabaeidae) infected with Oryctes rhinoceros nudivirus in oil palm and coconut plantations - Anggraini, Erise; Vadamalai, Ganesan; Kong, Lih Ling; Mat, Mazidah; Lau, Wei Hong (Nature Research, 2023)
The CRB (coconut rhinoceros beetle) haplotype was classified into CRB-S and CRB-G, based on the presence of single nucleotide polymorphisms (SNPs) in the mitochondrial cox1 gene. Mitochondrial genomes (mitogenomes) are the most widely used genetic resources for molecular evolution, phylogenetics, and population genetics in relation to insects. This study presents the mitogenome CRB-G and CRB-S which were collected in Johor, Malaysia. The mitogenome of CRB-G collected from oil palm plantations in 2020 and 2021, and wild coconut palms in 2021 was 15,315 bp, 15,475 bp, and 17,275 bp, respectively. The CRB-S was discovered in coconut and oil palms in 2021, and its mitogenome was 15,484 bp and 17,142 bp, respectively. All the mitogenomes have 37 genes with more than 99% nucleotide sequence homology, except the CRB-G haplotype collected from oil palm in 2021 with 89.24% nucleotide sequence homology. The mitogenome of Johor CRBs was variable in the natural population due to its elevated mutation rate. Substitutions and indels in cox1, cox2, nad2 and atp6 genes were able to distinguish the Johor CRBs into two haplotypes. The mitogenome data generated in the present study may provide baseline information to study the infection and relationship between the two haplotypes of Johor CRB and OrNV in the field. This study is the first report on the mitogenomes of mixed haplotypes of CRB in the field.